Ideational Meaning of Material Process in EFL Students’ Problem-Solving Text: A Frame of Systemic Functional Linguistics - Veronika Listi Ferdini Damopolii; Eva Tuckyta Sari Sujatna; Dadang Suganda; Rosaria Mita Amalia (Qubahan Academic Journal)
The background of this research is centered on the writing text of students learning English as a Foreign Language (EFL) in Eastern Indonesia, where students face challenges in expressing their ideas because of the lack of effective teaching methods. This study aims to improve EFL students' problem-solving text writing and express their idea by helping them develop ideas grounded in their personal experiences. To achieve this, the research focuses on analysing ideational meaning through transitivity, participants, processes, and circumstances, in Systemic Functional Linguistics, to know students’ ideas through writing. Qualitative and quantitative method were used to analyze the data. The main result adduces ideational meanings in material process represent problems and solutions, such as indifference, defection, negligence, abandonment, laziness, fatigue, breakthrough, hope, struggle, persistence, pride, achievement, determination, courage, and encouragement. Most frequently used participant is I, referring to most of these students and the problems and solutions they face and implement. The most widely used circumstances are time and accompaniment. This research result is different from the theory raised by Gerot and Wignell, which state that the most dominant circumstances and tense in expository text are time, cause and present. Additionally, past tense forms are observed in some clauses in the problem-solution texts. The theoretical contribution of this study is to apply SFL as a model of language use that use material processes to obtain ideational meaning as a function, while the practical contribution is to help students be more courageous in writing English and to express their ideas, experiences and goals more easily. The pedagogical contribution of this study is to apply SFL as a model and use descriptive language to examine how linguistic choices reflect social contexts and their functions in students' lives in advancing their learning.